2011
DOI: 10.1186/1477-5956-9-55
|View full text |Cite
|
Sign up to set email alerts
|

Enriched sera protein profiling for detection of non-small cell lung cancer biomarkers

Abstract: BackgroundNon Small Cell Lung Cancer (NSCLC) is the major cause of cancer related-death. Many patients receive diagnosis at advanced stage leading to a poor prognosis. At present, no satisfactory screening tests are available in clinical practice and the discovery and validation of new biomarkers is mandatory. Surface Enhanced Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (SELDI-ToF-MS) is a recent high-throughput technique used to detect new tumour markers. In this study we performed SELDI-ToF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…Our and Bowler's studies have demonstrated the feasibility of using SELDI as a diagnostic test for COPD, and that the serum protein fingerprint of COPD patients is different from that of healthy people. This permits to reveal low abundance proteins in serum and plasma samples, as needed for biomarker discovery [26][27][28]. However, our research results differ from those of Bowler's study.…”
Section: Discussioncontrasting
confidence: 57%
“…Our and Bowler's studies have demonstrated the feasibility of using SELDI as a diagnostic test for COPD, and that the serum protein fingerprint of COPD patients is different from that of healthy people. This permits to reveal low abundance proteins in serum and plasma samples, as needed for biomarker discovery [26][27][28]. However, our research results differ from those of Bowler's study.…”
Section: Discussioncontrasting
confidence: 57%
“…The high-throughput nature and simplicity of its experimental procedures make SELDI-TOF MS a promising technology for future secretome analysis and biomarker discovery [47,48].…”
Section: Technologies Involved In Proteomicsmentioning
confidence: 99%
“…However, if plasma is pre-treated with ProteoMiner, species can be detected down to as low as 10 pg protein per mL, with an increment of sensitivity of up to three orders of magnitude. Clear advantages in accessing the low-abundance plasma proteome via CPLL treatment have also been reported by Beseme et al [31] and other groups [16,[32][33][34][35][36][37][38] who claimed the importance of early-stage biomarkers. Although after a few years of use CPLLs did not yet generate validated protein markers, a number of scientific reports place a realistic discovery/validation hope very high.…”
Section: Sounding the Plasma (Serum) Proteomementioning
confidence: 75%